1 of 91 of 9 Items
Question
Multiple Choice
Solve the following problem: –43 + 17 =
(1 point)
Responses
60
60
26
26
–26
–26
–60
–60
Skip to navigation
13 answers
The correct answer is -26.
2 of 92 of 9 Items
Question
Solve the following problem: –20 – 65 + 4 =
(1 point)
Responses
–81
–81
–89
–89
89
89
49
49
Skip to navigation
Question
Solve the following problem: –20 – 65 + 4 =
(1 point)
Responses
–81
–81
–89
–89
89
89
49
49
Skip to navigation
The correct answer is -81.
Simplify the following expression: 121 ÷ 11 + 3 ∙ 4 ÷ 2
(1 point)
Responses
15
15
4.32
4.32
28
28
17
17
Skip to navigation
(1 point)
Responses
15
15
4.32
4.32
28
28
17
17
Skip to navigation
To simplify the expression, follow the order of operations (PEMDAS/BODMAS):
121 ÷ 11 + 3 ∙ 4 ÷ 2
First, perform the division:
= 11 + 3 ∙ 4 ÷ 2
= 11 + 12 ÷ 2
Next, perform the multiplication:
= 11 + 6
Finally, perform the addition:
= 17
The simplified expression is 17.
121 ÷ 11 + 3 ∙ 4 ÷ 2
First, perform the division:
= 11 + 3 ∙ 4 ÷ 2
= 11 + 12 ÷ 2
Next, perform the multiplication:
= 11 + 6
Finally, perform the addition:
= 17
The simplified expression is 17.
Simplify the following expression: 21(x – 4) + 2
(1 point)
Responses
21x – 2
21 x – 2
107x
107 x
21x – 82
21 x – 82
27x
27 x
Skip to navigation
(1 point)
Responses
21x – 2
21 x – 2
107x
107 x
21x – 82
21 x – 82
27x
27 x
Skip to navigation
To simplify the expression, distribute the 21 to the terms inside the parentheses:
21(x - 4) + 2
= 21x - 84 + 2
= 21x - 82
The simplified expression is 21x - 82.
21(x - 4) + 2
= 21x - 84 + 2
= 21x - 82
The simplified expression is 21x - 82.
Solve the following equation: 5x – 102 = 13
(1 point)
Responses
23
23
–23
–23
–17.8
–17.8
17.8
17.8
Skip to navigation
(1 point)
Responses
23
23
–23
–23
–17.8
–17.8
17.8
17.8
Skip to navigation
To solve the equation 5x - 102 = 13, you need to isolate the variable x.
First, add 102 to both sides of the equation:
5x - 102 + 102 = 13 + 102
5x = 115
Next, divide both sides of the equation by 5:
5x/5 = 115/5
x = 23
The solution to the equation is x = 23.
First, add 102 to both sides of the equation:
5x - 102 + 102 = 13 + 102
5x = 115
Next, divide both sides of the equation by 5:
5x/5 = 115/5
x = 23
The solution to the equation is x = 23.
6 of 96 of 9 Items
Question
Solve the following equation: 2x – 31 = 3(x + 2)
(1 point)
Responses
37
37
–37
–37
5
5
Image with alt text: thirty-seven over five
Skip to navigation
Question
Solve the following equation: 2x – 31 = 3(x + 2)
(1 point)
Responses
37
37
–37
–37
5
5
Image with alt text: thirty-seven over five
Skip to navigation
To solve the equation 2x - 31 = 3(x + 2), you need to distribute the 3 to terms inside the parentheses:
2x - 31 = 3x + 6
Next, subtract 2x from both sides of the equation:
2x - 2x - 31 = 3x - 2x + 6
Simplifying, we have:
-31 = x + 6
Subtract 6 from both sides of the equation:
-31 - 6 = x + 6 - 6
Simplifying further:
-37 = x
So, the solution to the equation is x = -37.
2x - 31 = 3x + 6
Next, subtract 2x from both sides of the equation:
2x - 2x - 31 = 3x - 2x + 6
Simplifying, we have:
-31 = x + 6
Subtract 6 from both sides of the equation:
-31 - 6 = x + 6 - 6
Simplifying further:
-37 = x
So, the solution to the equation is x = -37.
Find the range of the function f(x) = 4x – 1 for the domain {–1, 0, 1, 2, 3}.
(1 point)
Responses
{–5, –3, 0, 7, 11}
{–5, –3, 0, 7, 11}
{–5, –4, –3, –2, –1}
{–5, –4, –3, –2, –1}
{–11, –7, –3, 1, 5}
{–11, –7, –3, 1, 5}
{–5, –1, 3, 7, 11}
{–5, –1, 3, 7, 11}
Skip to navigation
(1 point)
Responses
{–5, –3, 0, 7, 11}
{–5, –3, 0, 7, 11}
{–5, –4, –3, –2, –1}
{–5, –4, –3, –2, –1}
{–11, –7, –3, 1, 5}
{–11, –7, –3, 1, 5}
{–5, –1, 3, 7, 11}
{–5, –1, 3, 7, 11}
Skip to navigation
To find the range of the function f(x) = 4x - 1 for the given domain {–1, 0, 1, 2, 3}, we need to calculate the corresponding values of f(x) for each x in the domain.
For x = -1:
f(-1) = 4(-1) - 1 = -4 - 1 = -5
For x = 0:
f(0) = 4(0) - 1 = 0 - 1 = -1
For x = 1:
f(1) = 4(1) - 1 = 4 - 1 = 3
For x = 2:
f(2) = 4(2) - 1 = 8 - 1 = 7
For x = 3:
f(3) = 4(3) - 1 = 12 - 1 = 11
Therefore, the range of the function f(x) = 4x - 1 for the given domain is {-5, -1, 3, 7, 11}. The correct response is {–5, –1, 3, 7, 11}.
For x = -1:
f(-1) = 4(-1) - 1 = -4 - 1 = -5
For x = 0:
f(0) = 4(0) - 1 = 0 - 1 = -1
For x = 1:
f(1) = 4(1) - 1 = 4 - 1 = 3
For x = 2:
f(2) = 4(2) - 1 = 8 - 1 = 7
For x = 3:
f(3) = 4(3) - 1 = 12 - 1 = 11
Therefore, the range of the function f(x) = 4x - 1 for the given domain is {-5, -1, 3, 7, 11}. The correct response is {–5, –1, 3, 7, 11}.